2014
DOI: 10.1021/ef5018708
|View full text |Cite
|
Sign up to set email alerts
|

Valuable Crude Oil from Hydrothermal Liquefaction of an Aliphatic Coal

Abstract: Artificial maturation techniques, like hydrothermal liquefaction (HTL) have demonstrated the ability to generate petroleum-like products, termed bio-oils, from feedstocks including manure, algae and agricultural wastes; however the oxygen, nitrogen and sulfur content of bio-oils often requires upgrading. The objective of this study was to utilize HTL on a low rank coal to produce a high quality crude oil sample that can be used as a transportation fuel. Coal from the WyodakAnderson coal seam was selected for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 92 publications
(212 reference statements)
0
8
0
Order By: Relevance
“…This result could be mainly attributed to the hydro‐denitrogenation treatment during second‐staged DCL. Hartman and Hatcher () found that NCCs in the expelled oil from coal hydrothermal liquefaction account for only 1% relative abundance among all the assigned classes. A series of NCCs including the N 1 , N 2 , N 1 O 1 , and N 1 O 2 classes were characterized in a DCL residue through solvent extraction followed by positive‐ion ESI FT‐ICR MS analysis of the extracts (Li et al, ).…”
Section: Class Chemicals Revealed By Ft‐icr Ms In Cdlsmentioning
confidence: 99%
See 4 more Smart Citations
“…This result could be mainly attributed to the hydro‐denitrogenation treatment during second‐staged DCL. Hartman and Hatcher () found that NCCs in the expelled oil from coal hydrothermal liquefaction account for only 1% relative abundance among all the assigned classes. A series of NCCs including the N 1 , N 2 , N 1 O 1 , and N 1 O 2 classes were characterized in a DCL residue through solvent extraction followed by positive‐ion ESI FT‐ICR MS analysis of the extracts (Li et al, ).…”
Section: Class Chemicals Revealed By Ft‐icr Ms In Cdlsmentioning
confidence: 99%
“…In comparison to NCCs, only one publication involve SCCs characterization in DCL products with FT‐ICR MS by Hartman & Hatcher (). They identified the S 1 O o (o = 1–12) class species in the expelled oil from coal hydrothermal liquefaction with negative‐ion ESI FT‐ICR MS and the S 1 O 1 ‐ S 1 O 3 class species are predominant.…”
Section: Class Chemicals Revealed By Ft‐icr Ms In Cdlsmentioning
confidence: 99%
See 3 more Smart Citations